1991
DOI: 10.1136/oem.48.4.286
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of hydrogen sulphide: a case of subacute manifestations and long term sequelae.

Abstract: mmHg, pH 7-45, So2 96%. The patient remained asymptomatic except for a residual exertion dyspnoea after five months. Blood parameters had returned to normal values but lung volumes and DLCO were still low five months after the admittance. Our diagnosis from this background was pneumonitis produced by inhalation of toxic gas. After the reported accident the toilet facilities were closed and the Generalitat de Catalunya Occupational Health Department carried out an investigation two days later. The autopsy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 2 publications
2
20
0
1
Order By: Relevance
“…However, this ®nding may be signi®cant and supports the observation of Parra et al [1991] which was based on a single case report. It is suggested that an isolated reduction in RV may represent a sub-acute manifestation of H 2 S intoxication.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…However, this ®nding may be signi®cant and supports the observation of Parra et al [1991] which was based on a single case report. It is suggested that an isolated reduction in RV may represent a sub-acute manifestation of H 2 S intoxication.…”
Section: Resultssupporting
confidence: 85%
“…Owens et al [1987] in a study of 69 patients noted this ®nding in a group of 11 subjects who had inhaled potentially toxic substances including ammonia, sulfur dioxide, and pesticides. Parra et al [1991] suggested the development of a mild ®brosis, with some decrease in lung volumes and gas transfer, subsequent to H 2 S inhalation while Green et al [1991] have demonstrated that exposure to H 2 S may adversely affect the properties of pulmonary surfactant.…”
Section: Discussionmentioning
confidence: 97%
“…These sources include toilets [Parra et al, 1991], sewers [Richardson, 1995;Watt et al, 1997], and liquid manure pits [Osbern and Crapo, 1981;Donham et al, 1982]. Some of these reports describe exposure-related pulmonary injuries that investigators attribute to hydrogen sulfide toxicity.…”
Section: Other Pulmonary Effectsmentioning
confidence: 94%
“…The usual levels of exposure to H,S in these trades are very low (0.5-10 ppm) [Parmeggiani, 19831. The lack of research on the long-term health effects of low level H,S exposure has been acknowledged by NIOSH [ 19771 as a barrier to establishing well-informed personal exposure limits. Nonetheless, several authors have suggested that low level H,S exposure may lead to decreased lung function [Parra et al, 1991;Zuskin et al, 19931. Hydrogen sulfide dissociates on contact with water to form caustic sulfides; therefore, it can irritate the mucous membrane of the respiratory system.…”
Section: Introductionmentioning
confidence: 99%